The threshold level of urinary cadmium associated with increased urinary excretion of retinol-binding protein and β2-microglobulin: a re-assessment in a large cohort of nickel-cadmium battery workers. Issue 4 (8th October 2010) - Chaumont, Agnès; De Winter, Frédéric; Dumont, Xavier; Haufroid, Vincent; Bernard, Alfred
Abstract : Objective: To evaluate the threshold value of urinary cadmium (CdU) for renal dysfunction on the basis of relationships unconfounded by protein degradation, diuresis and the renal effects associated with chronic smoking. Methods: We studied 599 workers (451 men, mean age 45.4 years) who were employed in four nickel-cadmium battery plants for 18.8 years on average. After adjustment for covariates by multiple regression, the CdU threshold values for increased concentrations of retinol-binding protein (RBPU) and b2 -microglobulin (b2 -mU) were assessed by logistic regression and benchmark dose analyses using as referents workers with CdU<1 μg/g creatinine. Results: Relationships between urinary proteins and CdU (μg/g creatinine) were influenced by sex, age, diuresis and especially smoking. When considering all workers, odds for abnormal RBPU and b2 -mU were significantly increased from CdU of 6-10 and >10, respectively. The benchmark dose (BMD5) and the benchmark dose lower limit (BMDL5) for a 5% excess in the background prevalence of abnormal RBPU and b2 -mU were estimated at 5.1/3.0 and 9.6/5.9. When excluding ever smokers, odds for abnormal RBPU and b2 -mU were both increased only among workers with CdU>10 (OR, 21.8, 95% CI, 6.4-74.4 and OR, 15.1, 95% CI, 3.6-63.1, respectively). In never smokers, these BMD5/BMDL5 of CdU were estimated at 12.6/6.6 and 12.2/5.5 while in ever smokers they were 6.2/4.9 and 4.3/3.5. Conclusions: On the basis of associations undistorted by smoking and adjusted for covariates, the BMDL5 of CdU for low-molecular-weight proteinuria induced by occupational exposure to Cd can be reliably estimated between 5.5 and 6.6 μg/g creatinine.